(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the shared foundation of simultaneous and consecutive interpretation, two essential methods for facilitating communication across language barriers. Despite their distinct execution, both forms of interpretation rely on a core set of skills and ethical principles that enable them to effectively convey meaning and foster cross-cultural understanding. The analysis reveals that both methods share a common goal: to ensure accurate and faithful translation of spoken messages, while prioritizing ethical practices, language proficiency, cultural sensitivity, and the crucial role of contextual understanding. By highlighting these shared foundations, this article underscores the vital role that both simultaneous and consecutive interpretation play in fostering effective communication and bridging the linguistic divide in an increasingly interconnected world.